Feature engineering descriptors, transforms, and machine learning for grain boundaries and variable-sized atom clusters - C. Braxton Owens; Nithin Mathew; Tyce W. Olaveson; Jacob P. Tavenner; Edward M. Kober; Garritt J. Tucker; Gus L. W. Hart; Eric R. Homer (npj Computational Materials)
Abstract Obtaining microscopic structure-property relationships for grain boundaries is challenging due to their complex atomic structures. Recent efforts use machine learning to derive these relationships, but the way the atomic grain boundary structure is represented can have a significant impact on the predictions. Key steps for property prediction common to grain boundaries and other variable-sized atom clustered structures include: (1) describing the atomic structure as a feature matrix, (2) transforming the variable-sized feature matrix to a fixed length common to all structures, and (3) applying a machine learning algorithm to predict properties from the transformed matrices. We examine how these steps and different combinations of engineered features impact the accuracy of grain boundary energy predictions using a database of over 7000 grain boundaries. Additionally, we assess how different engineered features support interpretability, offering insights into the physics of the structure-property relationships.